"It's me who supports. How are you going to refuse to have a child?”: the social norms and gender dynamics of men’s engagement in family planning practices in the Democratic Republic of the Congo - Salomine Ekambi; Kathryn Sugg; Florence Mpata; Dédé Marachto Aliango; Peter J. Winch (Reproductive Health)
Abstract Background In the Democratic Republic of the Congo (DRC), a disparity exists in the fertility desires of men and women, with men often expressing a desire for more children than their partners. This disconnect can be attributed to social and gender norms that influence discussions and decision-making regarding birth spacing, birth limiting, and the adoption of modern contraceptive methods. This qualitative study, through semi-structured interviews and focus group discussions, explored the social norms shaping perceptions, attitudes, and decision-making around family planning among men in the DRC. Methods The study protocol was adapted from the 5-step process set forth in the Social Norms Exploration Tool (SNET). Data collection took place in the three provinces of Kasai Central, Lualaba, and Sankuru. This process was divided into three phases: a reference-group identification phase incorporating a short, quantitative questionnaire, an exploration of norms and attitudes with the population of interest (N = 317) – here married and unmarried men – and further exploration of social norms among the reference groups (N = 144) cited by men. Results Social norms around family planning are contradictory and can be better understood by breaking down the concept of family planning into three categories of descriptive and injunctive norms: 1) the use of modern contraceptive methods, 2) birth spacing and family size, and 3) couple communication and decision-making. We found that while social norms oppose the use of modern contraceptive methods and advocate for larger family size, there is notable social support for birth spacing. Some men reported they would support their wives in learning about contraceptive methods if they were able to make the final decision. However, other men felt that allowing their wives to seek a method would undermine their authority or their virility. Conclusions To increase modern contraceptive uptake, interventions should address the underlying issues that contribute to non-adherence, addressing the three categories and their associated norms individually and engaging reference groups important to each, including healthcare providers, religious leaders, and male peer groups, in family planning programming.